Teens Impulsively React rather than Retreat from Threat - Dreyfuss, Michael; Caudle, Kristina; Drysdale, Andrew T.; Johnston, Natalie E.; Cohen, Alexandra O.; Somerville, Leah H.; Galván, Adriana; Tottenham, Nim; Hare, Todd A.; Casey, B.J. (Developmental neuroscience, 2014)
There is a significant inflection in risk taking and criminal behavior during adolescence, but the basis for this increase remains largely unknown. An increased sensitivity to rewards has been suggested to explain these behaviors, yet juvenile offences often occur in emotionally charged situations of negative valence. How behavior is altered by changes in negative emotional processes during adolescence has received less attention than changes in positive emotional processes. The current study uses a measure of impulsivity in combination with cues that signal threat or safety to assess developmental changes in emotional responses to threat cues. We show that adolescents, especially males, impulsively react to threat cues relative to neutral ones more than adults or children, even when instructed not to respond. This adolescent-specific behavioral pattern is paralleled by enhanced activity in limbic cortical regions implicated in the detection and assignment of emotional value to inputs and in the subsequent regulation of responses to them when successfully suppressing impulsive responses to threat cues. In contrast, prefrontal control regions implicated in detecting and resolving competing responses show an adolescent-emergent pattern (i.e. greater activity in adolescents and adults relative to children) during successful suppression of a response regardless of emotion. Our findings suggest that adolescence is a period of heightened sensitivity to social and emotional cues that results in diminished regulation of behavior in their presence.